On IPO Withdrawal - HELBING, PIA (Trinity College Dublin. School of Business. Discipline of Business & Administrative Studies, 2019)
This doctoral thesis offers insights into the determinants, outcomes and predictions of IPO withdrawal in 21st-century Western Europe by focusing on three distinct investigations. These investigations are motivated by a comprehensive literature review and underpinned by an overview of the European IPO setting. An integrative database is created on completed and withdrawn IPO filings from 2001 to 2017 in France, Germany, Italy, Spain and the UK. Regulatory, economic and market conditions as well as offer, firm and corporate governance characteristics are explored. The first investigation establishes the IPO withdrawal as a common feature of the main markets in Europe. Most companies that withdraw blame unfavourable market conditions; however, IPO offer and corporate governance characteristics emerge to be the main drivers of IPO withdrawal. A pronounced alignment of the determinants of IPO withdrawal is revealed under the lens of European equity market integration. The second investigation focuses on the determinants and timing of the different post-IPO withdrawal outcomes: private, inactive, M&A and trading. It is suggested that the IPO is one of several alternatives in which private equity and venture capital pursue a dual-track strategy. Better corporate governance at the time of the IPO filing reduces the probability of a negative post-withdrawal outcome. Little evidence on second time IPOs disregards the market timing arguments. The third investigation suggests that IPO withdrawal can be predicted and is not random. It is demonstrated that there are common determinants of IPO withdrawal shared by all European IPOs, regardless of the particular stock exchange or country of domicile. Superior post-IPO withdrawal outcomes exhibit a higher predicted IPO withdrawal probability which implies a dual-track strategy. Finally, the three investigations in this thesis provide compelling results to answer the set of specific research questions. Additional and potential inquiries are identified for future research throughout the thesis.
Determinants, Outcomes and Predictions in 21st Century Western Europe
APPROVED
Keywords: IPO; IPO Withdrawal; Europe; M&A; Probit; Survival; Private Equity